2019
DOI: 10.1111/hae.13898
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of Glanzmann's thrombasthenia and factor VII deficiency due to a combination of pathogenic and non‐pathogenic gene variants

Abstract: Gp IX (%)99.2Factor VII:C (IU/dL) 22Factor IX:C (IU/dL) 135 F7 genotype Homozygous c.-323_313insCCTATATCCT -122T>C and R353Q polymorphisms ITGB3 genotype Heterozygous variants Q158L and K676T Note: Normal range (NR) for coagulation factors: 50%-150%. | e27LETTER TO THE EDITOR one diagnosis, no further tests are performed. This leads to incomplete diagnosis on most of the occasions. The second interesting point which needs to be highlighted is that it is a practice to attribute the factor deficiency to a pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“… 107 It is becoming more and more clear that bleeding in GT depends not only on the mutations that define the pathology but involves variants of a wide variety of genes involving coagulation factors and the vasculature as previously discussed for other IPDs. 77 , 78 For example, Deshpande et al 108 identified a combination of GT and mild FVII deficiency in a 13-yr-old Indian boy with GT and a moderately severe bleeding syndrome. His platelets lacked αIIbβ3 due to compound heterozygosity for p.Q132K and p.K650T in ITGB3 .…”
Section: How Other Gene Defects Can Modify the Gt Phenotypementioning
confidence: 99%
“… 107 It is becoming more and more clear that bleeding in GT depends not only on the mutations that define the pathology but involves variants of a wide variety of genes involving coagulation factors and the vasculature as previously discussed for other IPDs. 77 , 78 For example, Deshpande et al 108 identified a combination of GT and mild FVII deficiency in a 13-yr-old Indian boy with GT and a moderately severe bleeding syndrome. His platelets lacked αIIbβ3 due to compound heterozygosity for p.Q132K and p.K650T in ITGB3 .…”
Section: How Other Gene Defects Can Modify the Gt Phenotypementioning
confidence: 99%